Activation time analysis and electromyographic fatigue in patients with temporomandibular disorders during clenching. Issue 4 (August 2015) - Pitta, Natássia Condilo; Nitsch, Gabriel Silva; Machado, Mariana Barcellos; de Oliveira, Anamaria Siriani
Abstract Introduction: The use of surface electromyography (SEMG) is controversial in the diagnosis and subsequent treatment of temporomandibular disorders (TMD), although there is some evidence that the pattern of the masticatory muscles in TMD patients differs from controls. The aim of this study was to compare relative time of mandibular elevator muscle activation at different levels of activity and median frequency (MF) during sustained clenching. Methods: Twenty-two women, aged between 18 and 48 years, volunteered to participate in the study. The TMD group had 14 participants diagnosed as group Ia muscle disorders (RDC/TMD). The control group had eight healthy individuals. SEMG records were obtained from masseter and temporal muscles during 10 s of sustained clenching. Normalized SEMG amplitudes were classified as minimal, moderate and maximal and time of activation in each level of activity was calculated and compared using two-way ANOVA (groups versus time). A slope of the linear regression line that fits MF values over time was calculated as a fatigue index for elevator muscles. Results: Only the temporal muscles of the TMD group showed longer activation time at moderate and minimal activity levels compared to controls. Fatigue indexes were greater for the TMD group compared to controls. Conclusion: Results showed motor control strategies during sustained clenching that differentiate controls from TMD patients.